2000
DOI: 10.1190/1.1444882
|View full text |Cite
|
Sign up to set email alerts
|

Advanced inversion methods for airborne electromagnetic exploration

Abstract: Airborne electromagnetic (AEM) surveys can contribute substantially to geologic mapping and target identification if good-quality multifrequency data are produced, properly evaluated, and displayed. A set of multifrequency EM data is transformed into a set of apparent resistivity (ρ a ) and centroid depth (z * p ) values, which then are plotted as a sounding curve. These ρ a (z * p ) curves commonly provide a smoothed picture of the vertical resistivity distribution at the sounding site. We have developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 16 publications
0
70
0
1
Order By: Relevance
“…A few authors have suggested to perform a full inversion of the EMI data without assuming the LIN approximation [29][30][31], but it is our impression that this is not common practice. For airborne instruments of a similar type, the industry standard has been to perform a full processing and inversion of the data [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…A few authors have suggested to perform a full inversion of the EMI data without assuming the LIN approximation [29][30][31], but it is our impression that this is not common practice. For airborne instruments of a similar type, the industry standard has been to perform a full processing and inversion of the data [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of several 1-D inversion procedures is presented by [19]. In this paper, the procedures described by [7] are used.…”
Section: Calculation Of Resistivity Modelsmentioning
confidence: 99%
“…To interpret the AEM data in terms of layered-earth resistivity models the Marquardt-Levenberg 1-D inversion technique [6] and [7] is used.…”
Section: Instrumentation For Airborne Em Surveysmentioning
confidence: 99%
“…The algorithm provides dual interpretation parameters (apparent resistivity and apparent depth) at each frequency. Formal (non-linear, least-squares) inversion of AEM data is becoming more widespread (Sengpiel and Siemon, 2000) and a multilayer inversion (Beamish, 2002b), restricted to a half-space assessment, is used here to provide models of the subsurface resistivity distribution.…”
Section: The Airborne Em Techniquementioning
confidence: 99%